Examining Cash Waqf from the Perspectives of Malaysian Actual Donors - Amin, Hanudin; Jam, Nor Syakina; Ring, Patrick J; Suhartanto, Dwi; Mai, Muhamad Umar; Razak, Dzuljastri Abdul; Shaikh, Imran Mehboob (International Journal of Islamic Economics and Finance (IJIEF), 2024)
This study examined the cash waqf giving behaviour in Malaysia covering Selangor, Perak, Negeri Sembilan and Pahang. The theory of planned behaviour (TPB) was employed as a point of departure to observe the factors influencing the cash waqf behaviours involving 777. SPSS 27 was then utilised to assess and consider the data to test hypotheses and draw statistical conclusions. The TPB’s factors were instrumental in shaping the expansion of cash waqf giving in Malaysia. The added variable, Islamic altruism was also statistically influential and played an important role in determining the behaviour formation.  Besides, in the post hoc analyses, we discovered a mediating role of attitude for the tested and examined independent variables involved. The usefulness of the results obtained was confined to the theory used as well as the geographical areas chosen. The results obtained can be learned by Malaysian waqf institutions to further strengthen the waqf collections by optimising the significant variables found in this study. This study is the first to check the effects of the TPB's factors in the context of actual behaviour, which adds more knowledge to the existing waqf literature available in the world.